Effect of the practice of assessment in augmenting creativity: perspective of the TESL, educational management and leadership, and visual art learners / Jacqueline Susan Rijeng and Imelia Laura Daneil - Rijeng, Jacqueline Susan; Daneil, Imelia Laura (Universiti Teknologi MARA, Kedah, 2016)
The emphasis on developing creativity in Malaysian institutions of higher education has brought significant changes to assessment practices in higher education today. A study was conducted to explore postgraduate students’ perceptions of assessment and the influence of classroom assessment practices on students’ creativity. A conceptual framework was built, based on the integration of convergent and divergent thinking coined by Guilford (1950) as well as Bloom’s taxonomy (1956) which underpins the assessment approaches. The study employed a mixed method research design and involved a group of final year full-time postgraduate students (n=40) from three different programmes in the Faculty of Education, Universiti Teknologi MARA (UiTM), Shah Alam. Findings revealed that students had a positive attitude to assessment as an integral aspect in the classroom, particularly in relation to the transparency of assessment (M = 4.114, SD = 0.648). Interestingly, oral presentation was perceived to be one of the best assessment methods as it could develop creative ability, suggesting that presentations could be conducted creatively. The findings have implications for curriculum development across different programmes in order to develop creativity in higher education.